NATIONAL POLICY OF THE RUSSIAN STATE: ELIBERATIONS ON PUTIN’S ARTICLE - AKAEV, Vakhit (CENTRAL ASIA AND THE CAUCASUS, 2012)
On January 23, 2012, Nezavisimaia gazeta carried an article by Prime Minister of Russia Vladimir Putin entitled “Russia: The National Question,” which took the Russian public by surprise. Indeed, this was the first time in his twelve years on the political Olympus that the Russian leader had turned to the national question. The article invited very contradictory opinions and sent waves in all directions. The presidential candidate (he was elected president a couple of months later) tried to analyze various aspects of national relations in Russia—a fact which in itself deserves the close attention of the expert community. And it was with this aim that I too took up the pen. I live in the Chechen Republic, the most complicated and conflict-prone constituency of the Russian Federation (part of the North Caucasian Federal District, which also includes the Stavropol Territory and all of the North Caucasian republics, with the exception of Adigey, which belongs to the Southern Federal District).